RENT SEEKING PRACTICE : A NEW CORRUPTION CULTURE WITHIN INDONESIAN POLITICION AND BIROCRATION - Widanarto Widanarto (Jurnal Politikom Indonesiana, 2017)
Abstract The practice of rent seeking is a new cultural phenomenon of corruption in Indonesiasince implementation of government reform and regional autonomy. The culture is the caseamong the corruption of public officials and politicians collaborated with entepreuneurs andpeople who interested in the effort to get around the cracks of public policy for the benefit ofserving and enriching themselves. The practice of rent seeking can take place in various activities of government andpolitics from the sale of official promotion and recruitment, the budget of allocation forprogramme activities and government projects, political compromise in the formulation anddetermination of public policy, political compromise ahead of the elections or regionalelections and many more. The practice of rent seeking can not be eliminated as long as the state does notimplement a democratic political system, upholding the rule of law or law enforcement, welfare oriented development and social justice, and that is no less important is a decisiveleadership, visionary, honest, and legitimate without any political engineering. Keywords : Rent Seeking, Corruption, Democracy and Rule of Law